Auxiliary agent for improving catalytic cracking propylene yield and preparation method thereof
By acid extraction of MFI structure molecular sieve under low pH conditions and mixed slurry with phthalid slurry, the existing catalytic cracking additives are solved, and the effect of improving propylene yield and wear resistance is achieved.
Patent Information
- Application Number
- CN202110173335.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-08
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-02-08
AI Technical Summary
The existing catalytic cracking additives have insufficient performance in improving propylene yield, and the preparation process is complex, with problems such as hard agglomeration and hardening of the adhesive, which affects the anti-wear performance and pore structure of the additives.
Under lower pH values of 0.1 to 1.7, the MFI structure molecular sieve is acid extraction treated with organic acid and/or inorganic acid to reduce the particle size of the molecular sieve and clear the pores. At the same time, the slurry is mixed with the slurry and acid to modify the molecular sieve and binder to simplify the preparation process.
It improves the propylene yield and the anti-wear properties of the additives, increases the pore volume, simplifies the preparation process, and avoids the problems of binder curing and hard molecular sieve agglomeration.
Smart Images

Figure BDA0002938845350000111 
Figure BDA0002938845350000121 
Figure BDA0002938845350000122
Abstract
Description
Technical Field
[0001] The invention relates to a catalytic cracking aid, in particular to a catalytic cracking aid for improving the yield of catalytic cracking propylene and a preparation method thereof. Background Art
[0002] Judging from the current market situation of the refining industry, diesel demand has dropped significantly, and the world gasoline will reach its peak around 2020. In contrast to the oversupply of oil products, my country's production capacity of low-carbon olefins such as ethylene and propylene is insufficient, and the equivalent consumption gap is still large. In terms of ethylene, it is estimated that the ethylene production capacity will reach about 30 million tons / year in 2020, but at the same time, with the increase in demand for ethylene downstream products, the equivalent consumption will reach about 46.5 million tons, and it is still necessary to import about 20 million tons of ethylene downstream derivatives. In terms of propylene, with the increase in demand for propylene downstream products, it is estimated that the propylene production capacity will reach about 42 million tons / year in 2020, but there is still a gap of about 7 million tons in equivalent consumption. Therefore, China's refining industry urgently needs to transform and upgrade from "fuel type" to "chemical type" and adjust its structure to cope with it, digest excess production capacity, activate redundant assets, and turn to continuous strengthening with the courage of pioneering and innovation to improve corporate competitiveness. For most catalytic cracking units, the use of catalysts or additives with MFI structure zeolites is an effective technical approach to increase propylene production.
[0003] CN 1465527A discloses a MFI structure zeolite containing phosphorus and transition metals. The anhydrous chemical expression of the zeolite is (0-0.3)Na2O·(0.5-5)Al2O3·(1.3-10)P2O5·(0.7-15)M2O3·(70-97)SiO2, calculated by the mass of the oxides, wherein M is selected from one of the transition metals Fe, Co and Ni. When the zeolite is used in the catalytic cracking process of petroleum hydrocarbons, the yield and selectivity of C2-C4 olefins can be improved, and the yield of liquefied gas is higher.
[0004] CN 1796496A discloses a cracking aid for increasing the concentration of propylene, which is composed of 10-65 wt% of modified ZSM-5 molecular sieve, 0-60 wt% of clay, 15-60 wt% of inorganic oxide binder, 0.5-15 wt% of one or more metal additives selected from Group VIIIB metals and 2-25 wt% of phosphorus additive on a dry basis, wherein the modified ZSM-5 molecular sieve is modified by phosphorus and a metal selected from Fe, Co or Ni, and the mass of the oxide is (0-0.3)Na2O·(0.5-5)Al2O3·(1.3-10)P2O5·(0.7-15)M x O y·(70~97)SiO2. This additive is used in the catalytic cracking process to increase the yield of liquefied gas and the octane number of gasoline, while significantly increasing the propylene concentration in the liquefied gas.
[0005] CN 102049284 B discloses a catalytic cracking propylene additive and a preparation method thereof. The additive contains 30 to 80 weight percent of molecular sieves based on a total weight of 100 percent, wherein the content of ZSM-5 zeolite is 28 to 78 weight percent, and the content of clay is 10 to 65 weight percent. The additive contains P, which is 5.0 to 20.0 weight percent, preferably 7.0 to 15.0 weight percent, in terms of P2O5, and the content of La2O3 is 0 to 1.0 weight percent. Aluminum phosphate sol is used as a binder to improve the wear resistance of the additive, improve the solid content of the spray slurry, and avoid the chlorine content on the spray slurry and the additive. The prepared catalytic cracking propylene additive has good dry gas and coke selectivity, and improves the propylene yield and the gasoline octane number.
[0006] CN 106179470A discloses a method for preparing a catalytic cracking additive for improving the octane number of gasoline, and the preparation steps are as follows: (1) slurrying ZSM-5 molecular sieve with water, controlling the solid content to 35-45wt%, adding a certain proportion of modifier, and stirring evenly. (2) adding a certain proportion of pseudo-boehmite to the slurry of step (1), and adjusting its pH value to 1.8-2.3 with acid solution. (3) adding a certain concentration of pseudo-boehmite slurry to a certain concentration of phosphoric acid solution, controlling the reaction temperature to 50-65°C, and the reaction time to >5h. (4) adding a certain amount of water to the slurry of step (3), and then adding kaolin, and stirring evenly. (5) adding the slurry in step (2) to the slurry in step (4), and stirring evenly. (6) spray drying to obtain the additive. Industrial tests have shown that the additive accounts for 3-10wt% of the system reserves, and the research octane number can be increased by 1-3 units, and the propylene yield can be increased by 1-4 percentage points. The silicon-aluminum ratio of the ZSM-5 molecular sieve in the additive is 100-300.
[0007] CN 108726535 A discloses a method for preparing a phosphorus-modified ZSM-5 molecular sieve with multi-level pores, comprising the following steps: uniformly mixing an aluminum source, an alkali, an organic template and deionized water, then adding a silicon source and a boron source, crystallizing the obtained mixed sol, recovering the crystallized product and removing the template to obtain a NaZSM-5 molecular sieve; then performing ammonium ion exchange to remove Na ions, and treating the obtained NH4-ZSM-5 molecular sieve with water vapor to obtain a deboronized molecular sieve; then impregnating with a phosphorus compound solution, and then drying and calcining to obtain a phosphorus-modified ZSM-5 molecular sieve with multi-level pores. The invention has the beneficial effects that the ZSM-5 molecular sieve prepared by the invention is used as a cracking catalyst adjuvant, which can solve the problems of low catalyst cracking activity and low yield of low-carbon olefins in the existing catalytic cracking process, obtain highly selective propylene, and improve product composition.
[0008] CN 107971029 A discloses a catalytic cracking aid for increasing propylene production and a preparation method thereof. The catalytic cracking aid for increasing propylene production comprises, based on the dry weight of the aid, 10-75 weight % of a phosphorus-containing MFI structure molecular sieve in dry weight, 3-40 weight % of a phosphorus-aluminum inorganic binder in dry weight, 1-30 weight % of other inorganic binders in oxides, 0-60 weight % of a second clay in dry weight, and 0.5-15 weight % of a metal additive selected from at least one of Group VIII metals and manganese, zinc and gallium in oxides. The preparation method comprises: mixing the phosphorus-containing MFI structure molecular sieve, the phosphorus-aluminum inorganic binder and the other inorganic binders, adding or not adding the second clay, beating the pulp, and spray drying; wherein the metal additive is introduced, and the phosphorus additive is introduced or not. At the same time, the proportion of the mesopore volume of the phosphorus-containing MFI structure molecular sieve to the total pore volume is 40-70% by volume, and the proportion of the mesopore volume with a pore size of 2 nanometers to 20 nanometers to the total mesopore volume is more than 85% by volume; the proportion of the strong acid content of the molecular sieve to the total acid content is 45-75%, and the ratio of the B acid content to the L acid content is 8-30. The preparation method uses the phosphorus-containing MFI structure molecular sieve as a raw material, but the phosphorus-containing MFI structure molecular sieve needs to be processed by processes such as dealumination, phosphorus modification and roasting, and these processes directly affect the pore volume, pore size and other properties of the phosphorus-containing MFI structure molecular sieve, and the processing process of the molecular sieve of the invention is relatively cumbersome. In addition, the method also uses a phosphorus-aluminum inorganic binder as a raw material, and the binder solidification phenomenon is prone to occur during the preparation process of the phosphorus-aluminum inorganic binder, which means that the addition speed of phosphoric acid must be strictly controlled during production, and the production conditions and environment are demanding. At the same time, due to the high pH value during the preparation process, it is not conducive to the dealumination process of the molecular sieve.
[0009] Although the existing preparation technology of additives has solved some deficiencies and met the needs of additives in some aspects, the existing zeolite molecular sieves have been treated with metal and / or non-metal modification, roasting, etc., and the molecular sieve modification process is complicated. The modified molecular sieve has the problem of hard agglomeration, and it is also necessary to grind and other treatments to reduce its particle size before it can be used for the preparation of additives, otherwise it is not conducive to the anti-wear performance of the additives; the existing technology or separately prepares aluminum phosphate sol, and the concentration of phosphorus and aluminum in the preparation process is high, and there may be colloid instability and gelation, which is not conducive to the smooth production of additives; the use of pre-prepared aluminum phosphate to prepare catalytic cracking additives often has the problems of small pore volume and large bulk ratio, which is not conducive to fluidization, mass transfer and scorching. The additives prepared by the existing technology also need to be further improved in terms of the performance of improving propylene yield. Therefore, in order to meet the requirements of reducing the difficulty of additive production, improving the performance of additives such as increasing propylene production, and ensuring smooth production, despite the recent additive technology for improving the catalytic cracking propylene yield, there is still a need for a new technology for preparing propylene additives with simple and feasible preparation process and further improved performance. Summary of the invention
[0010] The purpose of the present invention is to avoid the shortcomings of the above-mentioned technology, and to provide an additive and a preparation method thereof for improving the catalytic cracking propylene yield that are different from the existing methods. The method of the present invention is conducive to removing non-framework aluminum that blocks the molecular sieve pores under the condition of a low pH value of 0.1 to 1.7 in the presence of organic acid and / or inorganic acid, reducing the particle size of the molecular sieve, and making the molecular sieve more dispersible; at the same time, the molecular sieve is added before the pseudo-boehmite is acidified, and then mixed with the pseudo-boehmite and acid for pulping, so as to achieve the purpose of both dispersing the pseudo-boehmite and acid-modifying the molecular sieve, so that the prepared catalytic cracking additive has good anti-wear performance and unobstructed pore structure, which is more conducive to the contact between the reactant molecules and the active center of the molecular sieve and the timely diffusion of the product molecules away from the molecular sieve, reducing the occurrence of over-cracking and side reactions. The additive of the present invention does not need to prepare aluminum phosphate colloid separately, nor does it need to be treated by impregnation, filtration, roasting, etc. on the molecular sieve. The preparation process is simple, the prepared additive has a large pore volume and good anti-wear performance, and can significantly improve the propylene yield.
[0011] The additive for improving the yield of propylene by catalytic cracking disclosed in the present invention contains, based on the mass of the additive as 100%, 10-55% of H-type and / or NH4-type MFI structure molecular sieves with a silicon oxide / aluminum oxide molar ratio of 15-95 on a dry basis, 10-55% of clay on a dry basis, 3-20% of pseudo-boehmite on a dry basis, 5-20% of phosphorus on an oxide basis, 0-10% of a binder on an oxide basis, and 0.2-6% of a modified metal compound on an oxide basis. The additive is obtained by the following preparation method: before the pseudo-boehmite is acidified, the MFI structure molecular sieve is added to form an acidified colloid with a pH value of 0.1-1.7; the acidified colloid is homogenized and directly spray-dried and roasted to obtain the additive for improving the yield of propylene by catalytic cracking.
[0012] The additive for improving the catalytic cracking propylene yield disclosed in the present invention contains, based on 100% of the additive mass, 20-45% of MFI structure molecular sieves calculated on a dry basis, 15-40% of clay calculated on a dry basis, 5-15% of pseudo-boehmite calculated on a dry basis, 10-18% of phosphorus calculated on an oxide basis, 0-5% of a binder calculated on an oxide basis and 0.3-4% of a modified metal compound calculated on an oxide basis.
[0013] The auxiliary agent for improving the yield of propylene by catalytic cracking disclosed in the present invention, wherein the clay is at least one selected from kaolin, metakaolin, sepiolite, rectorite, montmorillonite and diatomite; the binder is at least one selected from alumina sol and aluminum chloride; the phosphorus is at least one selected from phosphoric acid, diammonium hydrogen phosphate, diammonium phosphate and ammonium phosphate; the modified metal compound is at least one selected from transition metal compounds and metal compounds of Group IIIB in the periodic table. The transition metal compound is at least one selected from compounds containing Fe, Ni, Cu, Mn or Zn, including halides, nitrates, sulfates of water-soluble transition metal elements, oxides, hydroxides, carbonates of water-insoluble transition metal elements, as one or more thereof. The IIIB group metal in the periodic table is selected from one or more of Y and lanthanide rare earths, and the lanthanide rare earth is selected from at least one of lanthanum-rich rare earths, cerium-rich rare earths, pure lanthanum or pure cerium, including water-soluble halides, nitrates, sulfates, compounds rich in IIIB group elements, and water-insoluble oxides, hydroxides, and carbonates of IIIB group elements, as one or more thereof.
[0014] The preparation method of the auxiliary agent for improving the yield of propylene by catalytic cracking disclosed in the present invention can be as follows: MFI structure molecular sieve, water, modified metal compound, clay and acid are mixed and slurried for 15min to 120min to obtain mixed slurry A, wherein the pH value of slurry A is 0.1 to 1.7. Then pseudo-boehmite is added to slurry A to form slurry B, and the pH value of slurry B is adjusted to 0.1 to 1.7 with acid, and then aged at 40 to 60° C. for 30min to 60min, cooled to below 35° C., and then a binder and a phosphorus compound are added, homogenized, spray-dried and roasted to obtain the auxiliary agent for improving the yield of propylene by catalytic cracking.
[0015] In the above process, the MFI structured molecular sieve is mixed with acid for slurrying. After the non-framework aluminum that blocks the pores in the molecular sieve is extracted by acid, the particle size of the molecular sieve is reduced and the pores are more unobstructed; at the same time, the modified metal compound and the molecular sieve undergo ion exchange to modify the molecular sieve. Pseudoboehmite and acid are added to slurry A to form slurry B, so that the pseudoboehmite is peptized and dispersed. At the same time, the MFI structured molecular sieve continues to contact with the acid to ensure that its non-framework aluminum is fully removed and the molecular sieve particles are fully dispersed. After the phosphorus compound and the binder are added, the phosphide reacts with the molecular sieve, pseudoboehmite, and the binder to achieve the purpose of phosphorus-modified molecular sieve, phosphorus-modified pseudoboehmite, and phosphorus-modified binder, so that the gelling system finally forms a stable and uniform colloid.
[0016] In the preparation process of the auxiliary agent for improving the propylene yield of catalytic cracking disclosed in the present invention, the formation of the slurry A can also be as follows: the MFI structure molecular sieve, water, and modified metal compound are mixed and slurried for 15 minutes to 45 minutes, so that the modified metal ions first modify the molecular sieve, and then phosphoric acid and / or at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and ammonium phosphate are added, and other acids, such as one or more of hydrochloric acid, nitric acid, and sulfuric acid, can also be added at the same time to modify the molecular sieve with phosphorus and acid-extract non-framework aluminum, and continue slurrying for 15 to 75 minutes to form slurry A.
[0017] The auxiliary agent for improving the propylene yield of catalytic cracking disclosed by the present invention can also be prepared by: mixing and slurrying MFI structure molecular sieve, water, modified metal compound, pseudo-boehmite, and clay, adding acid to form slurry C, making the pH value of slurry C in the range of 0.1 to 1.7, then aging at 40 to 60° C. for 30 to 120 minutes, cooling to below 35° C., adding binder and phosphorus compound, spray drying, and roasting to obtain the catalytic cracking auxiliary agent for improving the propylene yield. This preparation process is simple, MFI structure molecular sieve, water, pseudo-boehmite, clay, and acid to form slurry C, under acidic conditions of pH 0.1 to 1.7, the metal compound modified molecular sieve and the dispersion of molecular sieve and pseudo-boehmite are achieved, and the molecular sieve acid extracts non-framework aluminum and dredges the pores.
[0018] In the process of the present invention, phosphorus is directly added to the gelling system. Compared with the formation of aluminum phosphate colloid or phosphorus-containing MFI structure molecular sieve alone, the phosphorus-containing colloid is more stable and not easy to gel, probably because the concentration of phosphorus in the system is relatively low. Moreover, compared with the formation of aluminum phosphate colloid or phosphorus-containing MFI structure molecular sieve alone, the preparation process of the auxiliary agent of the present invention is simplified, and the prepared auxiliary agent has better anti-wear performance and larger pore volume.
[0019] The catalytic cracking aid for improving propylene yield disclosed in the present invention, wherein the acid used is at least one selected from hydrochloric acid, nitric acid, phosphoric acid, oxalic acid, citric acid, and formic acid; and the amount of acid added is such that the pH value of the mixed slurry A, slurry B, and slurry C is within the range of 0.1 to 1.7. If phosphoric acid is used to adjust the pH value of the mixed slurry A, slurry B, and slurry C, it is best to select at least one selected from hydrochloric acid, nitric acid, oxalic acid, citric acid, and formic acid to ensure that the pseudo-boehmite is fully dispersed, thereby ensuring that the aid of the present invention has good anti-wear performance.
[0020] The catalytic cracking aid for improving propylene yield disclosed in the present invention, wherein the binder can be added in any step of the gelling process, and is not limited by the order of addition. For example, it can be added before the pseudo-boehmite is acidified, or it can be added after the pseudo-boehmite is acidified.
[0021] The main advantages and effects of the present invention are:
[0022] The catalytic cracking aid disclosed in the present invention has the advantages that firstly, the raw material MFI structure molecular sieve of the present invention is simple and does not need to go through complicated processing steps such as dealumination, phosphorus modification and roasting. Only untreated raw material H-type and / or NH4-type MFI structure molecular sieve is needed, thereby saving the preparation cost of molecular sieve and aid.
[0023] Secondly, organic acid and / or inorganic acid, modified metal compound, in the presence or absence of pseudo-boehmite, H-type and / or NH4-type MFI structure molecular sieves with a silicon oxide / alumina molar ratio of 15 to 95 are modified with metal compounds and acid extraction treatment. The molecular sieve can be acid-treated together with pseudo-boehmite, or it can be acid-treated alone, and then further acid-treated together with pseudo-boehmite. Compared with the use of a higher pH value in the prior art, the present invention is treated at a lower pH value of 0.1 to 1.7. The specific surface area of the molecular sieve under this pH value environment is increased, and the increase in pore volume is conducive to dredging the pores of the molecular sieve, dispersing the molecular sieve and pseudo-boehmite. At the same time, the modified metal compound and the molecular sieve undergo ion exchange, thereby modifying the molecular sieve to obtain a catalytic cracking aid with improved reaction performance and anti-wear performance; metal compound modification can increase propylene yield and propylene selectivity. The additive of the invention does not require the molecular sieve to be impregnated, filtered, roasted, ground and crushed, etc., has a simple preparation process, and the colloid properties of the colloid are stable. The prepared additive has a large pore volume and good anti-wear performance, and can significantly improve the propylene yield.
[0024] Furthermore, the present invention does not require the pre-preparation of the phosphorus-aluminum inorganic binder, thereby simplifying the preparation process of the auxiliary agent. However, in the pre-preparation of the phosphorus-aluminum inorganic binder, the addition speed of phosphoric acid must be strictly controlled during production, which brings inconvenience in production and the problem of stable production. In the preparation process of the auxiliary agent of the present invention, the addition time of phosphoric acid is not very strictly limited, and the problem of binder curing is not easy to occur.
[0025] The catalytic cracking aid of the invention has good catalytic cracking performance and can effectively improve the propylene yield after being mixed with the main agent and used in the catalytic cracking reaction of hydrocarbon oil. DETAILED DESCRIPTION
[0026] The present invention is further described below with reference to examples, but the present invention is not limited to these examples.
[0027] (I) Analytical testing methods used in the examples.
[0028] 1. Sodium oxide, phosphorus, silicon oxide and aluminum oxide content: analyzed by X-ray fluorescence method.
[0029] 2. Specific surface area and pore volume: The test was conducted using the Autosorb-6B physical adsorption instrument produced by Quantachrome, USA. Before the test, the sample was pre-treated by vacuum degassing at 300°C for 8 hours to remove moisture and impurities in the sample, and then adsorption-desorption analysis was performed under liquid nitrogen temperature of 77K. The specific surface area and pore volume were calculated using the BET and BJH equations, respectively.
[0030] 3. The particle size of the molecular sieve was analyzed by laser particle size analyzer. The anti-wear performance of the catalytic cracking additive was analyzed by MS-C / 6 wear index analyzer produced by Shenyang Kehui Instrument Manufacturing Co., Ltd.
[0031] 4. Catalyst cracking reaction performance evaluation: It was carried out on the ACE-MODEL R+MM evaluation device. The catalyst was pre-treated at 800°C and 100% steam for 17 hours. The reaction raw material was 3 million tons / year of heavy catalyst crude oil from Lanzhou Petrochemical Company. The reaction conditions were a catalyst-to-oil ratio of 5.0 and a reaction temperature of 530°C.
[0032] (ii) Specifications of raw materials used in the examples.
[0033] 1. Kaolin (burning loss 18.6%), diatomite (burning loss 15.4%), pseudo-boehmite (burning loss 36.4%), aluminum sol (containing 21.2% by weight of aluminum oxide), low-silicon ZSM-5 molecular sieve (silicon-aluminum molar ratio 35, Na2O content 0.10%, crystallinity 84%, median particle size 8.0μm, specific surface area 350m 2 / g, pore volume 0.215mL / g), NaZSM-5 molecular sieve (silicon-aluminum molar ratio 35, Na2O content 2.98%): all are industrial products, collected from the catalyst plant of Lanzhou Petrochemical Company.
[0034] 2. Ferrophosphorus modified ZSM-5 molecular sieve (silicon to aluminum molar ratio 36, Na2O content 0.10%, P2O5 content 4.51%, Fe2O3 content 2.1%): prepared by the method disclosed in CN1465527A.
[0035] 3. Aluminum chloride, formic acid, oxalic acid, citric acid, nitric acid (>65% by weight), hydrochloric acid (concentration 36%), phosphoric acid (concentration 85%), diammonium phosphate, ferric chloride, manganese chloride, zinc nitrate, nickel nitrate, lanthanum chloride, lanthanum oxide, ammonia water (concentration 25-28%), sodium hydroxide, ammonium chloride: all are chemical reagents.
[0036] 4. Main catalyst: self-made, containing 33% (by weight) of Y-type molecular sieve, and the rest is binder, carrier material, rare earth. Activity of 72% after 17 hours.
[0037] Example 1 provides the MFI structured molecular sieve having the effect of the present invention.
[0038] Example 1
[0039] 50g of low-silicon ZSM-5 molecular sieve (dry basis) was added to 125mL of deionized water. Under stirring, 2.5g of oxalic acid was added. The pH value of the molecular sieve slurry was adjusted to 0.5 with hydrochloric acid. The mixture was stirred for 1h, then filtered, washed and dried. The molecular sieve Z-1 treated by the method of the present invention was obtained. The analysis showed that the molecular sieve Z-1 had a silicon-aluminum molar ratio of 37, a crystallinity of 87%, a median particle size of 7.0μm and a specific surface area of 358m 2 / g, pore volume 0.223mL / g.
[0040] Compared with the raw material low silicon ZSM-5 molecular sieve (silicon aluminum molar ratio of 35, crystallinity of 86%, median particle size of 8.0 μm), the silicon aluminum ratio and crystallinity of Z-1 molecular sieve are improved, and the median particle size is reduced, indicating that the acid treatment of the method of the present invention is helpful to remove non-framework aluminum in the molecular sieve and reduce the particle adhesion between the molecular sieves, thereby achieving the purpose of dispersing the molecular sieve. After the acid treatment, the specific surface area of the molecular sieve Z-1 is increased and the pore volume is increased, indicating that the acid treatment is conducive to dredging the pore structure of the molecular sieve and increasing the contactable surface of the molecular sieve.
[0041] Example 2
[0042] 1140g (dry basis) of low-silicon ZSM-5 molecular sieve was added to 2066mL of deionized water, mixed and slurried, 11.4g of citric acid and 46g of ferric chloride were added, the slurry pH value was 1.07, stirred for 45min, and then 100g of phosphoric acid was added, and stirring was continued for 15min. 2145mL of deionized water, 235g of aluminum chloride, 1006g (dry basis) of kaolin and 300g (dry basis) of pseudo-boehmite were added, and the slurry pH value was increased to 0.60. The temperature was raised to 50°C, stirred for 1 hour, and then cooled to 25°C. Under stirring, 521g of phosphoric acid was added, and stirring was continued for 30 minutes. The obtained colloid solid content was 37% (weight). After homogenization, it was spray-dried, formed and calcined to obtain the additive ZJ-1 of the present invention.
[0043] Comparative Example 1
[0044] 1140 g (dry basis) of low-silicon ZSM-5 molecular sieve was added into 2543 mL of deionized water, mixed and slurried to form molecular sieve slurry DJ-1.
[0045] 1642 mL of deionized water, 1020 g (dry basis) of kaolin and 300 g (dry basis) of pseudo-boehmite were mixed and slurried, and the pH value of the slurry was adjusted to 0.9 with 18% hydrochloric acid. The temperature was raised to 50°C and stirred for 1 hour. The temperature was then lowered to 25°C. Under stirring, molecular sieve slurry DJ-1 was added, followed by 235 g of aluminum chloride and 621 g of phosphoric acid. Stirring was continued for 30 minutes. The obtained colloid had a solid content of 37% (by weight). After homogenization, the colloid was spray-dried and calcined to obtain the comparative additive DZJ-1.
[0046] Comparative Example 2
[0047] The comparative auxiliary agent DZJ-2 was prepared according to the method of Example 1 of patent CN 1796496A.
[0048] Preparation of phosphate aluminum sol: 1050g of pseudo-boehmite was mixed with 3350mL of deionized water and slurried for 30min, 4900g of phosphoric acid was added to the slurry under stirring, the temperature was raised to 70°C, and then reacted at this temperature for 45min to prepare a colorless and transparent phosphate aluminum sol.
[0049] Take 1900g (dry basis) of phosphorus-iron modified ZSM-5 molecular sieve, 1250g (dry basis) of kaolin and 650g of pseudo-boehmite, add 6200mL of deionized water and 2790g of aluminum sol, and beat for 120min. Then add 1L of FeCl 3` 6H2O (containing 100g Fe2O3). The mixture was slurried for 45 minutes, and then 1220g of phosphorus aluminum sol was added to the mixed slurry. After stirring evenly, the obtained slurry was spray-dried, formed, and calcined to obtain the comparative additive DZJ-2.
[0050] Comparative Example 3
[0051] In this comparative example, 11.4 g of citric acid was not added. After the ferric chloride was added, the pH value of the slurry was adjusted to 4.0 with ammonia water. After the pseudo-boehmite was added, the pH value of the slurry was adjusted to 3.0 with ammonia water. The other steps were the same as those in Example 2 to obtain a comparative auxiliary agent DZJ-3.
[0052] Example 3
[0053] 1050 g (dry basis) of low-silicon ZSM-5 molecular sieve, 50 g of zinc nitrate, 21 g of lanthanum oxide, 1036 g (dry basis) of kaolin, and 360 g (dry basis) of pseudo-boehmite are added to 3523 mL of deionized water, mixed and slurried, and the pH value of the slurry is adjusted to 1.7 with 18% hydrochloric acid. The temperature is raised to 50° C. and stirred for 1 hour, then cooled to 25° C., 745 g of phosphoric acid is added while stirring, and stirring is continued for 30 minutes. The obtained colloid has a solid content of 40% (weight). After homogenization, it is spray-dried, formed, and roasted to obtain the additive ZJ-2 of the present invention.
[0054] Comparative Example 4
[0055] (1) Aluminum phosphate sol binder was prepared according to the method of Example 1 of patent CN 102049284B.
[0056] 3 kg of pseudo-boehmite (dry basis) was slurried with 5.4 kg of deionized water for 30 minutes. 10.3 kg of 85% concentrated phosphoric acid was added to the slurry under stirring, followed by 5.28 kg of 68% concentrated nitric acid. The reaction was continued with stirring for 45 minutes to obtain a phosphate aluminum sol.
[0057] (2) The comparative auxiliary agent DZJ-4 was prepared according to the method of Example 2 of patent CN 102049284B.
[0058] 1.18 kg of water was added to 1.05 kg (dry basis) of low-silicon ZSM-5 molecular sieve, and the mixture was homogenized to prepare ZSM-5 molecular sieve slurry.
[0059] Under stirring, 1.5 g (dry basis) of kaolin and 2.34 kg of water were mixed and slurried for 30 min, 1.5 kg of the binder prepared according to the method in step (1) was added to the kaolin slurry, and stirring was continued for 1 h, and then the ZSM-5 molecular sieve slurry was added and stirred for 2 h. After the slurry was homogenized, it was sprayed to obtain a comparative auxiliary agent DZJ-4 containing 35 wt% of ZSM-5 molecular sieve.
[0060] Example 4
[0061] 1350g (dry basis) low-silicon ZSM-5 molecular sieve, 8.7g manganese chloride, 14.7g nickel nitrate, 30g lanthanum chloride, 774g (dry basis) diatomaceous earth, and 210g (dry basis) pseudo-boehmite are added to 2800mL deionized water, mixed and slurried, 10g formic acid and 20g oxalic acid are added, and the pH value of the slurry is adjusted to 0.8 with 18% hydrochloric acid. The temperature is raised to 40°C, stirred for 1 hour, and then cooled to 30°C. Under stirring, 566g aluminum sol, 447g phosphoric acid, and 57g diammonium hydrogen phosphate are added, and stirring is continued for 50 minutes. The obtained colloid has a solid content of 45% (weight). After homogenization, it is spray-dried, formed, and roasted to obtain the additive ZJ-3 of the present invention.
[0062] Comparative Example 5
[0063] 1350g (dry basis) low-silicon ZSM-5 molecular sieve, 1320g (dry basis) diatomaceous earth, and 210g (dry basis) pseudo-boehmite were added to 2600mL deionized water, mixed and slurried, and the pH value of the slurry was adjusted to 0.8 with 18% hydrochloric acid. The temperature was raised to 40°C, stirred for 1 hour, and then cooled to 30°C. While stirring, 566g aluminum sol was added, and stirring was continued for 50 minutes. The obtained colloid had a solid content of 45% (weight). After homogenization, it was spray-dried, formed, and calcined to obtain the comparison additive DZJ-5.
[0064] Comparative Example 6
[0065] (1) Molecular sieve DA was prepared according to the method of Example 1 of patent CN 107971029 A.
[0066] Add 100g (dry basis) of NaZSM-5 molecular sieve to 1000g of 2.0% NaOH solution, heat to 65℃, react for 30min, quickly cool to room temperature, filter, and wash until the filtrate is neutral. Then, add 800g of water to the filter cake for slurrying, add 40g of NH4Cl, heat to 75℃, exchange for 1h, until the Na2O content is less than 0.2% by weight, filter, wash, and obtain a molecular sieve filter cake; take 50g (dry basis) of the above molecular sieve and add water to prepare a molecular sieve slurry with a solid content of 10% by weight, add 27g of oxalic acid during stirring; heat to 65℃ and stir at constant temperature for 1h, filter and wash until the filtrate is neutral; add water to the filter cake to obtain a molecular sieve slurry with a solid content of 40% by weight, add 6.1gH3PO4 (concentration 85% by weight), mix evenly, impregnate, dry, and calcine at 550℃ for 2 hours. Obtain molecular sieve DA.
[0067] (2) A phosphorus-aluminum inorganic binder was prepared according to the method of Example 4 of patent CN 107971029 A.
[0068] Pseudo-boehmite (containing 1.19 kg of Al2O3), kaolin (0.50 kg on dry basis) and 3.27 kg of decationized water were slurried for 30 minutes, and 5.37 kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring at a rate of 0.04 kg phosphoric acid / min / kg alumina source. The temperature was raised to 70°C and then reacted at this temperature for 45 minutes to obtain a phosphorus-aluminum inorganic binder.
[0069] (3) The comparative auxiliary agent DZJ-6 was prepared according to the method of Example 11 of patent CN 107971029 A.
[0070] Take molecular sieve DA, kaolin and pseudo-boehmite, add decationized water and aluminum sol to slurry for 120 minutes to obtain a slurry with a solid content of 30% by weight, add hydrochloric acid to adjust the pH value of the slurry to 3.0, then continue to slurry for 45 minutes, then add the phosphorus aluminum inorganic binder prepared in step (2), stir for 30 minutes, and then spray dry the obtained slurry to obtain microspheres. The microspheres are roasted at 500°C for 1 hour. Take the obtained microsphere product, add ZnCl2 aqueous solution (concentration 30% by weight), heat to 60°C with stirring, react at this temperature for 20 minutes, vacuum filter and dry the slurry, and then roast at 500°C for 2 hours to obtain the comparative auxiliary agent DZJ-6.
[0071] The additives ZJ-1 to ZJ-3 prepared by Examples 2 to 4 and the comparative additives DZJ-1 to DZJ-6 prepared by Comparative Examples 1 to 6 were tested for their pore volume and wear index, respectively, and the test results are listed in Table 1. From the data in Table 1, it can be seen that the preparation process of the catalytic cracking additive prepared by the method of the present invention is simple, and the obtained additive has good strength and high pore volume. Although the strength of the additives obtained by Comparative Examples 1, 2, and 4 can meet the use requirements, the pore volume is small; the additives obtained by Comparative Examples 3, 5, and 6 have a large pore volume, but poor strength.
[0072] Table 1 Physicochemical properties of additives
[0073]
[0074]
[0075] In order to investigate the cracking reaction performance of the additive, the main catalyst, additives ZJ-1 to ZJ-3 and comparative additives DZJ-1 to DZJ-6 were aged at 800°C and 100% steam for 10 hours, and then the additives were mixed with the main catalyst at a ratio of 5% (i.e., main catalyst: additive (weight ratio) = 95:5) for evaluation. The evaluation results are listed in Table 2. In Table 2, total liquid yield = liquefied gas + gasoline + diesel.
[0076] Table 2 Results of catalytic cracking reaction selectivity evaluation
[0077]
[0078] The data results in Table 2 show that: compared with the main catalyst, the propylene yield of the catalyst mixed with the catalytic cracking aids ZJ-1 to ZJ-3 provided by the present invention is significantly improved.
[0079] Compared with the catalyst mixed with the catalytic cracking aid ZJ-1 provided by the present invention, the propylene yield of the catalyst mixed with the comparative catalytic cracking aid DZJ-1 provided in Comparative Example 1 was reduced by 1.38 percentage points, indicating that the catalytic cracking aid prepared by the method of the present invention can significantly increase the propylene yield.
[0080] Compared with the catalyst mixed with the catalytic cracking aid ZJ-1 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-2 provided in Comparative Example 2 has a propylene yield reduced by 1.03 percentage points, and the coke yield is equivalent, indicating that the catalytic cracking aid prepared by the method of the present invention has good catalytic cracking selectivity and significantly improves the propylene yield.
[0081] Compared with the catalyst mixed with the catalytic cracking aid ZJ-2 provided by the present invention, the propylene yield of the catalyst mixed with the comparative catalytic cracking aid DZJ-3 provided in Comparative Example 3 was reduced by 0.45 percentage points, indicating that the pH value will affect the propylene yield. The propylene yield of the present invention is higher when the pH value is 0.1 to 1.7.
[0082] Compared with the catalyst mixed with the catalytic cracking aid ZJ-2 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-4 provided in Comparative Example 4 has a propylene yield reduced by 0.36 percentage points and a coke yield increased by 0.53 percentage points, and the coke yields are equivalent, indicating that the catalytic cracking aid prepared by the method of the present invention has good catalytic cracking selectivity and significantly improves the propylene yield.
[0083] Compared with the catalyst mixed with the catalytic cracking aid ZJ-3 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-5 provided in Comparative Example 5 has a propylene yield conversion rate reduced by 0.79 percentage points, a propylene yield reduced by 1.26 percentage points, and a coke yield increased by 0.15 percentage points, indicating that the catalytic cracking aid prepared by the method of the present invention has better activity stability, can improve catalytic cracking selectivity, and especially significantly improve propylene yield.
[0084] Compared with the catalyst mixed with the catalytic cracking aid ZJ-3 provided by the present invention, the propylene yield of the catalyst mixed with the comparative catalytic cracking aid DZJ-6 provided in Comparative Example 6 is reduced by 0.07 percentage points, indicating that compared with the prior art, the catalytic cracking aid prepared by the method of the present invention has a simple preparation process, does not require separate alkali, acid extraction and roasting process treatment to obtain the raw material molecular sieve, the aid has better anti-wear performance, and the propylene yield is improved.
Claims
1. An additive for improving the yield of propylene by catalytic cracking, characterized in that: Calculated based on the mass of the additive as 100%, it contains 10-55% of H-type and / or NH4-type MFI structure molecular sieves with a silicon oxide / aluminum oxide molar ratio of 15-95 on a dry basis, 10-55% of clay on a dry basis, 3-20% of pseudo-boehmite on a dry basis, 5-20% of phosphorus on an oxide basis, 0-10% of a binder on an oxide basis, and 0.2-6% of a modified metal compound on an oxide basis; and the 0-10% of the binder on an oxide basis does not take the left endpoint 0; (I) The preparation method of the auxiliary agent specifically comprises the following steps: The MFI structure molecular sieve, water, modified metal compound, clay and acid are mixed, the pH value is adjusted to 0.1-1.7, and the slurry is beaten for 15-120 minutes to obtain a mixed slurry A, pseudo-boehmite is added to obtain slurry B, the pH value of the slurry B is adjusted to 0.1-1.7 with acid, and then aged at 40-60° C. for 30-60 minutes, cooled to below 35° C., a binder and a phosphorus compound are added, homogenized, spray-dried, and calcined to obtain an additive for improving the yield of catalytic cracking propylene; or, (II) The preparation method of the auxiliary agent specifically comprises the following steps: MFI structure molecular sieve, water, modified metal compound, pseudo-boehmite and clay are mixed and slurried, acid is added to obtain slurry C, pH value of slurry C is adjusted to 0.1-1.7, then aged at 40-60°C for 30-120min, cooled to below 35°C, binder and phosphorus compound are added, spray dried and calcined to obtain an additive for improving catalytic cracking propylene yield.
2. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 1, characterized in that: Taking the mass of the additive as 100%, it contains 15-40% clay calculated on a dry basis, 5-15% pseudo-boehmite calculated on a dry basis, 10-18% phosphorus calculated on an oxide basis, 0-5% binder calculated on an oxide basis and 0.3-4% modified metal compound calculated on an oxide basis; and the 0-5% binder calculated on an oxide basis does not take the left endpoint 0.
3. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 1, characterized in that: The clay is at least one selected from kaolin, metakaolin, sepiolite, rectorite, montmorillonite and diatomaceous earth; the binder is at least one selected from alumina sol and aluminum chloride; the phosphorus is at least one selected from phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate; the modified metal compound is at least one selected from transition metal compounds.
4. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 3, characterized in that: The transition metal compound is at least one selected from compounds containing Fe, Ni, Cu, Mn or Zn.
5. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 3, characterized in that: The transition metal compound is at least one compound selected from the group IIIB metal compounds in the periodic table; the group IIIB metal in the periodic table is at least one compound selected from Y and lanthanide rare earths.
6. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 3, characterized in that: The transition metal compound is at least one selected from the group consisting of halides, nitrates, sulfates of water-soluble transition metal elements and oxides, hydroxides and carbonates of water-insoluble transition metal elements.
7. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 5, characterized in that: The compound of the IIIB group metal in the periodic table is at least one selected from the group consisting of water-soluble halides, nitrates, sulfates of the IIIB group elements and water-insoluble oxides, hydroxides, carbonates of the IIIB group elements.
8. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 1, characterized in that: In (I), the MFI structured molecular sieve, water, and modified metal compound are first mixed and slurried for 15 to 45 minutes, and then acid is added and mixed and slurried to form a mixed slurry A.
9. The auxiliary agent for improving the yield of catalytic cracking propylene according to claim 1, characterized in that: The acid is at least one selected from hydrochloric acid, nitric acid, phosphoric acid, oxalic acid, citric acid and formic acid.
Citation Information
Patent Citations
Catalytic cracking propylene additive and preparation method thereof
CN102049284B
Method for preparing auxiliary increasing gasoline octane number through catalytic cracking
CN106179470A
Catalytic cracking aid for increasing propylene yield, and preparation method thereof
CN107971029A
Method for preparing phosphorus modified ZSM-5 molecular sieve with hierarchical pores
CN108726535A
MFI structure molecular sieve containing phosphorus and transition metal
CN1465527A